Alienation and Violence in Beatriz Cabur’s Plays - Herrera Cárdenas, María (The Grove - Working Papers on English Studies, 2023)
In the last decades of the 21st century, the growing interest in legitimising contemporary Spanish female playwrights is evident in the context of contemporary feminist theories. This research explores Beatriz Cabur’s plays, published and performed nationally and internationally, insofar as they respond to some of the current feminist demands regarding trauma. This study delves into the need for appropriate critical and analytical models for the study of theatrical experimentalism, which, in addition to its academic value, addresses current feminist demands. The development of this study is supported by clear thematic links that are established, from which it is possible to delve into the implicit and explicit feminisms of contemporary Spanish theatre, as well as the shaping, development, and legitimisation of contemporary feminine identities.